2021
DOI: 10.3390/ijerph18126340
|View full text |Cite
|
Sign up to set email alerts
|

Unravelling the Role of Socioeconomic Forces in the Early Stage of COVID-19 Pandemic: A Global Analysis

Abstract: The COVID-19 pandemic has rapidly evolved into an acute health crisis with extensive socioeconomic and demographic consequences. The severity of the COVID-19 pandemic requires a refined (and more comprehensive) understanding of virus dissemination over space, transmission mechanisms, clinical features, and risk factors. In line with this assumption, the present study illustrates a comparative, empirical analysis of the role of socioeconomic and demographic dimensions in the early stages of the COVID-19 pandemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…The reason for this phenomenon is that the majority of participants were more than 20 years old. This age group, which includes university students and workers from all walks of life, is also the most active in social activities, reflecting the impact of the pandemic on the population, especially the main economic forces [17]. In 2021, six cities (Guangzhou, Shenzhen, Dongguan, Zhuhai, Foshan, and Zhanjiang) of Guangdong province were classified into medium-risk or high-risk regions, and most regions of Guangdong province were low-risk regions (Figure 2).…”
Section: Discussionmentioning
confidence: 99%
“…The reason for this phenomenon is that the majority of participants were more than 20 years old. This age group, which includes university students and workers from all walks of life, is also the most active in social activities, reflecting the impact of the pandemic on the population, especially the main economic forces [17]. In 2021, six cities (Guangzhou, Shenzhen, Dongguan, Zhuhai, Foshan, and Zhanjiang) of Guangdong province were classified into medium-risk or high-risk regions, and most regions of Guangdong province were low-risk regions (Figure 2).…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have sought to determine the demographic and socioeconomic risk factors of infections and deaths of COVID-19 in a jurisdiction. [ 25 , 26 ] A study on the state of New Mexico during the pre-vaccination months found that areas with greater percentages of American Indians and Alaska Natives had greater numbers of confirmed cases. [ 27 ] Another study of America concluded that counties with higher proportions of Black and Hispanic residents tended to have greater numbers of total deaths.…”
Section: Discussionmentioning
confidence: 99%
“…Naively, in the present era of abundant and widely available data, one could expect that most of these questions could be settled down by systematically comparing the COVID-19 numbers with various demographic and environmental parameters. However, while much progress in this direction has been made (e.g., (Adhikari and Yin, 2020; Allel et al, 2020; An et al, 2020; Gupta and Gharehgozli, 2020; Pan et al, 2020; Djordjevic et al, 2021b; Hradsky and Komarek, 2021; Lorenzo et al, 2021; Markovic et al, 2021; Perone, 2021; Rontos et al, 2021; Salom et al, 2021; Singh et al, 2021; Wang et al, 2022)), many methodological obstacles complicate this type of research and often lead to conflicting conclusions of otherwise similar studies.…”
Section: Introductionmentioning
confidence: 99%